Contextual exploration previous to an aversive event predicts long-term emotional consequences of severe stress - Girardi, Carlos E.; Tiba, Paula A.; Llobet, Gisela B.; Levin, Raquel; Abílio, Vanessa C.; Suchecki, Deborah (Frontiers in Behavioral Neuroscience, 2013)
Traumatic stress can lead to long-term emotional alterations, which may result in Posttraumatic Stress Disorder (PTSD). Fear reactions triggered by conditioned cues and exacerbated emotional arousal in face of non-conditioned stimuli are among the most prominent features of PTSD. We hypothesized that long-term emotional alterations seen in PTSD may depend on the strength of context-trauma association. Here, we investigated the contribution of previous contextual exploration to the long-term emotional outcomes of an intense foot shock in rats. We exposed male Wistar rats to a highly stressful event (foot shock, 2 mA, 1 s) allowing them to explore or not the chamber prior to trauma. We, then, evaluated the long-term effects on emotionality. Fear was assessed by the time spent in freezing behavior either upon re-exposure to trauma context or upon exposure to an unknown environment made potentially more aversive by presentation of an acoustic stimulus. Behaviors on the elevated-plus-maze and acoustic startle response were also assessed. The possibility to explore the environment immediately before the aversive event led to differential long-term emotional effects, including a heightened freezing response to re-exposure to context, blunted exploratory behavior, fear sensitization and exacerbation of the acoustic startle response, in contrast to the minor outcomes of the foot shock with no prior context exploration. The data showed the strong contribution of contextual learning to long-term behavioral effects of traumatic stress. We argue that contextual representation contributes to the robust long-term behavioral alterations seen in this model of traumatic stress.